SUKU JAWA DI DESA SRI AGUNG KABUPATEN TANJUNG JABUNG BARAT (1991-2011) - Molanda, Rifaldo; Yanto, Ferry (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2023)
This research purpose is to find out and describe the causes of the existence of Javanese tribesin Sri Agung Village, Batang Asam District, Tanjung Jabung Bara Regency, the development ofJavanese tribes from 1991 to 2011 in Sri Agung Village, Batang Asam District, West TanjungJabung Regency, and Javanese cultural changes that have occurred in Sri Agung Village,Batang Asam District, West Tanjung Jabung Regency. This research used history method.Researchers try to find historical data and facts related to problems regarding the title of thestudy. The conclusion obtained from this study is that the Javanese transmigrated to improvetheir standard of living, and finally their economy developed in the 90s towards 2000 when palmoil prices soared, in addition to economic development, the development of education alsofollowed their success. Javanese culture in wedding ceremonies and death memorials is stillgoing on but with adaptations to several supporting events.